THE EFFECTIVENESS OF REACT STRATEGY IN STEM LEARNING ON THE COMPREHENSION OF 3D GEOMETRIC CONCEPTS - Huda, Moh. Khoridatul; Rohman, Ahmad Fiki Fatkur; Setiawan, Dwi Candra (Science Education, Institut Agama Islam Negeri Ponorogo, 2024)
The REACT strategy (Relating, Experiencing, Applying, Cooperating, Transferring) is indispensable in STEM education, as it cultivates critical thinking, experiential learning, and practical application, all of which are foundational to effective STEM pedagogy. This research evaluates the effectiveness of the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) strategy with the STEM approach versus traditional learning methods on flat surfaces in shapes, specifically regarding students' comprehension of concepts. The study utilised pre-test and post-test experiments with two groups: an experimental class and a control class - selected randomly through the Randomised Pre-Test Post-Test Control Group Design approach. The research was conducted on grade VIII students of MTsN 2 Kediri. The VIII-A experimental class employed the REACT strategy with the STEM approach, while the VIII-C control class used conventional learning models. The N-Gain Score testing method evaluated the increase in students' comprehension of the mathematical concepts. The findings revealed that the experimental class had an average N-Gain Score of , while the control class had an average score of . The average score for comprehending mathematical concepts for the experimental and control classes was , respectively. The independent sample t-test demonstrated that the experimental class achieved significantly better results than the control class. The student response questionnaires indicated that the REACT learning model received an average score of , categorised as